INFLUENCE OF METEOROLOGICAL PARAMETERS ON THE OPERATION OF A GRID - CONNECTED PV SOLAR PLANT - Milosavljević, Dragana D (Bulletin of Natural Sciences Research, 2018)
Elementary description and information on a grid-connected photovoltaic solar power plant (PV plant) of 2 kWp installed in Niš and the influence of meteorological parameters on its operation are given in this paper. Besides, experimental results of the calculation of the energy efficiency, electrical energy generated and output power of this PV plant operating in the real climate conditions in 2017 are presented. The results regarding climate parameters and characteristic performance parameter of 2 kWp PV plant in Niš in 2017 are discussed and it was found that in 2017 annual energy efficiency of this PV plant was 10.63% and it decreased with the ambient temperature increasing.
Keywords: Ambient temperature; Energy efficiency; Photovoltaic solar power plant; Photovoltaic conversion; Solar radiation